Evaluation of the power distribution network: plug-in hybrid electric vehicle connected - Galarza-Linares , Jose (2021)
The evaluation of new technologies in the electrical system is relevant for the planning and operation of the electrical network, this allows to provide a quality electrical service to the final users and to preserve the operation of the electrical system. The present research analyzes the integration of plug-in hybrid electric vehicles (EVs) in the electric distribution network. The European low voltage 906 busbar electric system of the IEEE is used as a test system, considering the increase of the electric demand depending on the operation, charging time, technology and autonomy of this new mobility technology. Through an analytical-non-experimental methodology, the following factors were analyzed: voltage variation, electrical energy losses and increase in demand in the medium and long term. The results obtained show that for levels of irruption of this new technology it is necessary to repower the current electrical network to preserve the stable operating conditions of the electrical system and to comply with the regulations of the electrical sector, the results show that the massive and uncontrolled connection has a great impact on the operation of the electrical network.